Evidence-based clinical practice guidelines for chronic pancreatitis 2021 - Shimizu, Kyoko; Ito, Tetsuhide; Irisawa, Atsushi; Ohtsuka, Takao; Ohara, Hirotaka; Kanno, Atsushi; Kida, Mitsuhiro; Sakagami, Junichi; Sata, Naohiro; Takeyama, Yoshifumi; Tahara, Junko; Hirota, Morihisa; et al. (Journal of gastroenterology, 2022)
Background Chronic pancreatitis (CP) is defined according to the recently proposed mechanistic definition as a pathological fibro-inflammatory syndrome of the pancreas in individuals with genetic, environmental, and/or other risk factors who develop persistent pathological responses to parenchymal injury or stress. Methods The clinical practice guidelines for CP in Japan were revised in 2021 based on the 2019 Japanese clinical diagnostic criteria for CP, which incorporate the concept of a pathogenic fibro-inflammatory syndrome in the pancreas. In this third edition, clinical questions are reclassified into clinical questions, background questions, and future research questions. Results Based on analysis of newly accumulated evidence, the strength of evidence and recommendations for each clinical question is described in terms of treatment selection, lifestyle guidance, pain control, treatment of exocrine and endocrine insufficiency, and treatment of complications. A flowchart outlining indications, treatment selection, and policies for cases in which treatment is ineffective is provided. For pain control, pharmacological treatment and the indications and timing for endoscopic and surgical treatment have been updated in the revised edition. Conclusions These updated guidelines provide clinicians with useful information to assist in the diagnosis and treatment of CP.